2007
DOI: 10.1017/s1833367200003734
|View full text |Cite
|
Sign up to set email alerts
|

Managers in the firing line: Contributing factors to workplace bullying by staff – an interview study

Abstract: Workplace bullying is a phenomenon that is attracting increasing interest from researchers throughout the Western world. To date, most of the research into workplace bullying has focused on managers and colleagues as the perpetrators of bullying in the workplace. By contrast, little is known about ‘upwards bullying’, where managers are the targets. We argue that in order to more fully understand workplace bullying as a whole, the phenomenon of upwards bullying requires research attention. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 44 publications
1
69
0
Order By: Relevance
“…While debate regarding some elements of the criteria for bullying persists, it is widely accepted that for behaviours to be categorised as bullying they must be repeated and unreasonable Branch et al 2007). To help distinguish between situations of concern to health and safety and more innocuous behaviours, the notion that the behaviours must cause or have the potential to cause harm in order to be considered bullying, has become a regular inclusion in workplace bullying prevention guides (e.g.…”
Section: Workplace Bullyingmentioning
confidence: 99%
“…While debate regarding some elements of the criteria for bullying persists, it is widely accepted that for behaviours to be categorised as bullying they must be repeated and unreasonable Branch et al 2007). To help distinguish between situations of concern to health and safety and more innocuous behaviours, the notion that the behaviours must cause or have the potential to cause harm in order to be considered bullying, has become a regular inclusion in workplace bullying prevention guides (e.g.…”
Section: Workplace Bullyingmentioning
confidence: 99%
“…Yet, the direction of internal bullying in interpersonal instances is largely downwards (from superior to subordinate) (Branch et al, 2013;Einarsen et al, 2011), though horizontal (between peers) , upwards (subordinate to superior) (Branch, Ramsay, & Barker, 2007) and/or cross-level co-bullying (where peers and/or subordinates join superiors) (D'Cruz & Rayner, 2012) are also reported. In instances of depersonalized bullying, internal bullying moves downwards, with superiors implementing the organizational agenda and ensuring subordinates' compliance (D'Cruz, 2015).While supervisory and managerial layers generally deal with the workforce immediately below them in the organizational hierarchy, it is possible that levels are skipped as they attempt to deliver results mandated by the organization (D'Cruz, 2015).…”
Section: Varieties Of Workplace Bullyingmentioning
confidence: 99%
“…Organizational antecedents include organizational culture and climate, leadership, job design and work organization, and organizational change (Salin & Hoel, 2011), operating within the work-environment hypothesis where situational factors (Salin & Hoel, 2011) give rise to interpersonal bullying (D'Cruz, 2015). Destructive forms of leadership (Aasland, Skogstad, Notelaers, Nielsen, & Einarsen, 2010), role conflict (Hauge, Skogstad, & Einarsen, 2009), role ambiguity (Baillien, Rodriguez-Mun˜oz, van den Broeck, & De Witte, 2011), work overload (Branch et al, 2007), and job insecurity (De Cuyper, Baillien, & De Witte, 2009) have been identified. Stressful work conditions are a fertile ground for bullying to unfold.…”
Section: The Causes Of Workplace Bullyingmentioning
confidence: 99%
See 1 more Smart Citation
“…Doing such work while being violated adds to the emotional strain already inherent in their work. Because such workplaces are involved in continual change and improvement as part of the job, bullying may be more likely (Branch, Ramsay, & Barker, 2007). In healthcare research, MacIntosh, Wuest, Gray, and Cronkhite (2010) found that workplace bullying can change the meaning of work, making it more difficult to sustain the need or ability to "make a difference."…”
Section: Bullyingmentioning
confidence: 99%